Antarctic fungal endophytes as tool for the reintroduction of native plant species in arid zones - Fardella, Cristian; Oses, Rómulo; Torres-Díaz, Cristian; Molina-Montenegro, Marco A (BOSQUE, 2017)
Ecological restoration is the deliberate action that speeds recovery from a degraded system by direct or indirect human intervention. Xerophytic formations are among the most degraded ecosystems where low water availability makes reintroduction plans unsuccessful and extremely expensive. Roots inoculation with endophytic fungi has been reported as a successful strategy to maintain or improve the ecophysiological performance and survival in different species of shrubs and trees. In harsh environments, endophytes have been shown to provide benefits in terms of survival and growth for their associated vegetation. In this study, we showed that inoculation with endophytes isolated from plants growing in Antarctica improve survival and water use efficiency for irrigation on native species of xerophytic formations: Flourensia thurifera, Senna cumingii and Puya berteroniana. Overall, the presence of endophytes improved survival of all native species. Furthermore, the presence of endophytes improved water use efficiency for irrigation, reaching higher percentages of survival in plants with a reduction in the added water. The application of Antarctic endophytes could be considered a successful strategy for future projects and reintroduction programs in arid and semi-arid zones of Chile.